2021
DOI: 10.1007/s40121-021-00476-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Clinical Utility of Metagenomic Next-Generation Sequencing in the Diagnosis of Pulmonary Infection

Abstract: Introduction: We aimed to explore the realworld clinical application value and challenges of metagenomic next-generation sequencing (mNGS) for pulmonary infection diagnosis. Methods: We retrospectively reviewed the results of mNGS and conventional tests from 140 hospitalized patients with suspected pulmonary infections from January 2019 to December 2020. The sample types included bronchoalveolar lavage fluid, lung tissue by transbronchial lung biopsy, pleural effusion, blood, and bronchial sputum. Apart from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…Xie found that the most common co-infection was bacterial and fungal mixed infection, followed by bacterial and bacterial infection. 40 Wang found that the most common mixed pulmonary infection was virus and fungal mixed infection. 39 Legoff found that the most common mixed infection was bacterial and viral mixed infection.…”
Section: Discussionmentioning
confidence: 99%
“…Xie found that the most common co-infection was bacterial and fungal mixed infection, followed by bacterial and bacterial infection. 40 Wang found that the most common mixed pulmonary infection was virus and fungal mixed infection. 39 Legoff found that the most common mixed infection was bacterial and viral mixed infection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on high-throughput sequencing, metagenomic next-generation sequencing (mNGS) is thought to be a promising microbial identification technology because of its rapid cycles and high sensitivity. mNGS identifies and classifies a wide range of pathogens (including respiratory tract ( Xie et al., 2021 ), blood stream ( Jing et al., 2021 ), central nervous system ( Wilson et al., 2019 ), and prosthetic joints pathogens ( Thoendel et al., 2018 )), and is a widely used microbial test for infectious diseases, particularly for special and rare pathogens. It can also be used to analyze drug resistance genes and virulence factors in pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…However, in respiratory samples (e.g., sputum, BAL), many attempts remain in the verification phase due to the complex microbial community. Meanwhile, the detection performance of mNGS in pneumonia is not completely consistent in multiple studies [ 17 , 27 , 32 , 33 ]. Thus, although mNGS may have great potential for broad-spectrum surveillance or as a universal pathogen detection method, the results of mNGS should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 93%
“…Miao et al reported that mNGS is not better than culture in recognizing bacteria but has superior feasibility in detecting fungi [ 28 ]. However, some studies reported inconsistent conclusions [ 17 , 34 , 35 ]. Possible explanations for this divergence are due to different sample types and some different test conditions of mNGS and culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation